Implementation of AHP Method in Decision Support for Selecting Outstanding Students Case Study: Senior High School - Ari Puspita; Yuyun Yuningsih; Hilda Amalia; Ade Fitria Lestari (Jurnal Riset Informatika, 2020)
The research looks for excellence each student has to find out students who excel. Academic and non-academic achievements can be a benchmark for finding the best students. The research method used in this study is the survey research method, in which the writer will distribute the questionnaire to one of the High Schools with the target of the research being students and observing through the principal and teachers at the High School. This study uses the AHP (Analytical Hierarchy Process) method which is assisted by Expert Choice Software in making decisions regarding high-achieving students in high schools in the Tangerang area. AHP process by comparing one student with other student candidates based on predetermined criteria, also comparing between criteria, to find which criteria are more favored. The results of the processing of the Expert Choice Software in the form of graphic images that show superior students can be decided by decision-makers. Keywords: Survey, , Achievement